Array Failure Diagnosis and Active Compensation for Intelligent Reflecting Surfaces - Li, Xiao Yu; Tong, Mei Song (2021 IEEE International Symposium on Antennas and Propagation and USNC-URSI Radio Science Meeting (APS/URSI), 2021)
Aiming at the maintenance requirements of Intelligent Reflecting Surface (IRS) in practical application, this paper proposes an element failure diagnosis and radiation pattern active compensation to ensure the IRS continues to operate in a certain standard. Specifically, the joint diagnosis process is realized based on the compressed sensing algorithm combined with the element reflection amplitude and reflection phase data. The compensation process uses the reconfigurable characteristics of the remaining working elements and utilizes the improved genetic algorithm for sparse optimization. Through analysis and simulation, a potential feasible implementation plan is provided for the failure diagnosis and active compensation of the IRS, which reduces the maintenance cost and improves its engineering application value.